ANALYSIS OF CORPORATE SOCIAL RESPONSSIBILITY EFFECT TOWARD ORGANIZATIONAL COMMITMENT (Case Study PT. Bank Negara Indonesia (persero) Tbk.) - Farah Margaretha; Adie Nugroho (Business and Entrepreneurial Review, 2012)
The background of the research is shifting on business competition where company who has social performance had a competitif advantage compare to other. There is few company who see social performance from stake holder perspective, especially employees. How employees see CSR activity that been conducted by the company and how it motivated them to increase organizational commitment. The purpose of this paper is to examine the effect of (I). CSR activity to organizational commitment, (2) CSR and organizational commitment as the beliefs of an emplyee to the importance of CSR increase. The design of this research applied as quantitatif research to describe the relation of two variabel. Data collection are using quesioner, interview, and literature study. The selection sampel are using convenience sampling. Data analysis applied multiple regression analysis to measuring method on employee perception about CSR and the relation on the organizational commitment. The result of the research indicated that there is effect between CSR and Organizational Commitment and how the employees belief to the company policy on doing CSR. The findings are limited to some Small Medium Enterprise and Companies  under supervision of BNI as Mentoring (partnership)